Hierarchical linear models in education sciences: an application - Valente, Vítor (2012)
The importance of hierarchical structured data analysis, based on appropriate statistical models, is very well known in several research areas. In this paper we describe an application in Education Sciences: we have students grouped in classes belonging to schools, which in turn are scattered throughout the country. This grouped organization is labelled as a hierarchical or multilevel structure, and the models usually adopted for statistical analysis of this kind of data are hierarchical linear or multilevel models. The development of these models takes into account data variability within and among the hierarchical levels. We apply a hierarchical linear model (HLM) with two levels – students and schools – in order to identify relevant differences in student performance (10th grade high school in 2004/2005), considering three scientific subjects and comparing two different regions of Portugal: Coastal and Inland.